Проблема лінгвістичної специфіки українських прізвищ у працях антропонімістів ХХ–ХХІ ст. - Садова (Лісова), Лариса Олександрівна; Sadova (Lisova), Larysa O. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано погляди учених-ономастів на історію формування та лігнвістичну специфіку українських прізвищ. Окреслено здобутки вчених в опрацюванні проблем змістового наповнення терміна прізвище, вирізненні основних диференційних ознак прізвищ як різновиду антропонімів, хронологізації їхньої появи. Виокремлено лінгвальні особливості формування спадкових антропонімів, з’ясовано особливості впливу позамовних чинників на виникнення прізвищ. The article clarifies the approaches of antroponimists concerning the history of formation and linguistic specificity of Ukrainian surnames. The author offers insights into the scholars’ achievements in exploring the problem of the term «surname» meaning, highlighting the key distinctive features of surnames as a type of anthroponyms, and defines the chronology of their appearance. It has been specified that the process of establishing the family names was gradual and covered the following main stages: the emergence of a person’s two-word naming on a certain territory; stabilization of the basic word-formative types of modern surnames; juridical regulation of surnames. The author places importance on the lingual peculiarities of the inheritable anthroponyms formation, reveals the level of the extralinguistic factors’ influence on the appearance of surnames. Scientists’ conceptions and approaches concerning various characteristic aspects of this specific kind of anthroponyms have been systematized in the article.
The Problem of Linguistic Specification of Ukrainian Surnames in in the Works of Anthroponymists in XX–XXI Centuries
Keywords: прізвище; антропоніміка; антропонім; ономастика; surname; anthroponomy; anthroponym; onomastics